Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/cc11157
|View full text |Cite
|
Sign up to set email alerts
|

Failure to normalize lymphopenia following trauma is associated with increased mortality, independent of the leukocytosis pattern

Abstract: IntroductionFollowing trauma and systemic inflammatory response syndrome (SIRS), the typical response is an elevation of the total complete blood count (CBC) and a reduction of the lymphocyte count. This leukocytosis typically returns to normal within 48 hours. The persistence of a leukocytosis following trauma is associated with adverse outcomes. Although lymphocyte anergy and dysfunction following trauma is associated with increased risk for infection and sepsis, there is a paucity of data regarding the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
162
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(186 citation statements)
references
References 23 publications
10
162
1
Order By: Relevance
“…These findings support the notion that frailty is not strictly related to biological age and that the number of comorbidities does not fully correlate with their severity (Afilalo et al, 2012;Farhat et al, 2012;Fernández-Garrido et al, 2014a;Fried et al, 2004;Partridge et al, 2012;Robinson et al, 2013) As the frailty burden increases, the occurrence of one or more complications are more likely. Robinson et al (2013) reported that infection was the most common complication in both surgical groups, and perhaps related to this, a decrease in immune function has also been described in frail individuals (Furlan et al, 2013;Heffernan et al, 2012;Leng et al, 2009;Reddan et al, 2003). Length of hospital stay increased as the frailty burden accumulated, and thus these patients also accrued higher economic and health-professional costs during this postsurgical period (Cohen et al, 2012;Lasithiotakis et al, 2013;Lee et al, 2010;Makary et al, 2010;Robinson et al, 2013).…”
Section: Grade IIImentioning
confidence: 91%
“…These findings support the notion that frailty is not strictly related to biological age and that the number of comorbidities does not fully correlate with their severity (Afilalo et al, 2012;Farhat et al, 2012;Fernández-Garrido et al, 2014a;Fried et al, 2004;Partridge et al, 2012;Robinson et al, 2013) As the frailty burden increases, the occurrence of one or more complications are more likely. Robinson et al (2013) reported that infection was the most common complication in both surgical groups, and perhaps related to this, a decrease in immune function has also been described in frail individuals (Furlan et al, 2013;Heffernan et al, 2012;Leng et al, 2009;Reddan et al, 2003). Length of hospital stay increased as the frailty burden accumulated, and thus these patients also accrued higher economic and health-professional costs during this postsurgical period (Cohen et al, 2012;Lasithiotakis et al, 2013;Lee et al, 2010;Makary et al, 2010;Robinson et al, 2013).…”
Section: Grade IIImentioning
confidence: 91%
“…On the other hand, lymphocytes and crypt intestinal epithelial cells can be driven to apoptosis after severe trauma 38 . Furthermore, an inability to normalize posttraumatic lymphopenia in a timely fashion is associated with a poor outcome, irrespective of the dynamics of the leukocytosis 39 . Excessive immune, coagulatory and ROS responses can lead to substantial endotheliopathy and dysfunction of cellular barriers 40 that facilitate the transit and generation of more PAMPs and DAMPs, which amplifies a vicious cycle of tissue injury and damaging immunological processes 6,11,14 .…”
Section: Protective and Harmful Innate Immune Responses To Traumamentioning
confidence: 99%
“…Therefore, more information about the pathophysiology of this syndrome is needed if we are to better understand it and identify/develop novel clinical therapies. In this respect, studies have demonstrated that septic patients exhibited an impaired immunity associated with sustained loss of important immune cells (2,3). Several aberrations in leukocyte function have also been documented in septic patients, which are associated with poor outcome (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%